A realistic approach to explanation of the normal and reversed remanent magnetization of rocks: Application for submarine volcanics - ORLICKÝ, Oto (Contributions to Geophysics and Geodesy, 2010)
The results of the magnetic measurements and mineralogic data of the submarinebasalts and peridotites have been compared with the original model to explainthe origin of the normal and the reversed remanent magnetization (RM) of volcanics.According to the author the Ti-rich titano-magnetite (Ti-Mt) bearing rocks (without thesecondary magnetic phase) and the magnetite are always the carriers of only normal RM.The low-temperature oxidized Ti-Mt bearing rocks and those of the ilmenite-hematitebearing rocks of the deutheric oxidation origin (of the defined composition) are the carriersof dominantly reversed RM of the self-reversal origin. This idea have been approvedby many results of submarine volcanics, mostly basalts.